ANALISIS PENERAPAN KEWAJIBAN PERPAJAKAN PERUSAHAAN JASA KONSTRUKSI PADA PT. SARANA BANGUN PERKASA SURAKARTA - Widi Nurindah Sari; Fadjar Harimurti; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The Indonesian government is currently seeking equitable development, One of the government's efforts to obtain funds was obtained from tax collection. Construction Services is one of the activities in the economic, social, and cultural fields which have an important role in achieving various objectives to support the realization of national development. Data obtained from field observations, interviews, and questionnaires to measure the level of understanding of tax obligations. Data were analyzed using qualitative descriptive analysis. The results of the study indicate that the Tax Liability of PT. Sarana Bangun Perkasa Surakarta is Article 21 Income Tax , Article 23 Income Tax, Article 4 Income Tax Article 2, Value Added Tax (VAT) and Annual Tax Return. Calculation of tax liability rates is assessed based on the tax object in the Legislation. How to Deposit and Report Tax Obligations at PT. Sarana Bangun Perkasa Surakarta in 2017 is in accordance with the applicable law. while the time of depositing and reporting is not in accordance with the applicable law because during 2017 many are found not to be determined on time or late.